2017
DOI: 10.3389/fnins.2017.00220
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Malfunction in the Nervous System

Abstract: Neurodegenerative diseases often have multifactorial causes and are progressive diseases. Some are inherited while others are acquired, and both vary greatly in onset and severity. Impaired endoplasmic reticulum (ER) proteostasis, involving Ca2+ signaling, protein synthesis, processing, trafficking, and degradation, is now recognized as a key risk factor in the pathogenesis of neurological disorders. Lipidostasis involves lipid synthesis, quality control, membrane assembly as well as sequestration of excess li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 99 publications
0
19
0
Order By: Relevance
“…It has been reported that a deficiency in Fabp5 also protects against EAE (39,40). It is tempting to speculate that the calnexin/Fabp5 complex is a component of neuroproteostasis and lipidostasis (41). The dysregulation of calnexin/Fabp5 function may be a key event in the pathogenesis of MS and represents an important target for therapeutics development aimed at promoting favorable clinical outcomes for patients afflicted with MS.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a deficiency in Fabp5 also protects against EAE (39,40). It is tempting to speculate that the calnexin/Fabp5 complex is a component of neuroproteostasis and lipidostasis (41). The dysregulation of calnexin/Fabp5 function may be a key event in the pathogenesis of MS and represents an important target for therapeutics development aimed at promoting favorable clinical outcomes for patients afflicted with MS.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated cellular stress coping responses, including UPR and genome damage response, are drivers of multiple pathological conditions, ranging from cancer, neurodegeneration, inflammatory, and metabolic disorders 4 , 46 48 . In the case of ER stress, IRE1α initiates the most conserved signaling branch of the UPR which affects many cellular processes including cellular energetics 49 , 50 , inflammation 51 , immunity 52 , angiogenesis 53 , aging and longevity 54 , and neurodegeneration 4 , 31 , 55 58 . However, the molecular mechanism(s) responsible for cyclosporine-dependent activation of the UPR have long remained poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…All the enzymes involved in the de novo synthesis of sphingolipids normally reside in the ER (Breslow, 2013 ; Siow et al, 2015 ), which has long been strongly implicated in the pathology of HD (Jiang et al, 2016 ; Jung et al, 2017 ). Whether the dysfunctional sphingolipid synthesis reported in this study is a causing factor or a consequence of the ER abnormalities in HD cannot be clarified here.…”
Section: Discussionmentioning
confidence: 99%